Host-Guest Chemistry in Supramolecular Theranostics - Yu, Guocan; Chen, Xiaoyuan (Theranostics, 2019)
Macrocyclic hosts, such as cyclodextrins, calixarenes, cucurbiturils, and pillararenes, exhibit unparalleled advantages in disease diagnosis and therapy over the past years by fully taking advantage of their host-guest molecular recognitions. The dynamic nature of the non-covalent interactions and selective host-guest complexation endow the resultant nanomaterials with intriguing properties, holding promising potentials in theranostic fields. Interestingly, the differences in microenvironment between the abnormal and normal cells/tissues can be employed as the stimuli to modulate the host-guest interactions, realizing the purpose of precise diagnosis and specific delivery of drugs to lesion sites. In this review, we summarize the progress of supramolecular theranostics on the basis of host-guest chemistry benefiting from their fantastic topological structures and outstanding supramolecular chemistry. These state-of-the-art examples provide new methodologies to overcome the obstacles faced by the traditional theranostic systems, promoting their clinical translations.